Mechanism of Interaction of Adsorbent and Adsorbate - M.A. Mamadjonova; D.S. Salihanova; O.S. Karimov (International Journal on Orange Technologies, 2021)
Adsorption refining was carried out in the laboratory to determine the equilibrium time of the "oil-adsorbent" in a heterogeneous system. whitewashing process in activated Askamar bentonite (1) When carried out at 70 0 C, the chlorophyll content of the oil was absorbed at a rate of 0.2 mmol / g for up to 30 min, after which this value remained unchanged, as well as in Pakistan bentonite obtained for control, this value was 0.22 mmol / g.